THEORETICAL AND PRACTICAL ASPECTS OF APPLICATION OF ANTI-CRISIS MANAGEMENT TOOLS IN CONDITIONS OF UNCERTAINTY - HRABOVSKA Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the study of the features of the application of modern tools of anti-crisis management of the enterprise in conditions of uncertainty. The relevance of setting and solving a special research task of using an individual set of effective anti-crisis management tools for each enterprise and determining the patterns of forming one’s own trajectory in the strategy of preventing bankruptcy and directions for further development has been proven. The approach to the tasks of modern anti-crisis management, as a key factor in the formation of an enterprise - a self-developing microeconomic system, is substantiated. Attention is focused on the non-linear nature of the development of enterprises with sharp transformations at bifurcation points, which can lead to the process of the destruction of the company, or to its transition to a higher level of organization. It is emphasized that the application of analytical tools of homeostatics is also very important from a theoretical and practical point of view, as it allows to classify transitional periods in the business system according to the level of development and their participation in the processes of preventing bankruptcy of the enterprise. The transformation of the anti-crisis management system from the point of view of the systemic approach to the stability of the enterprise is considered. A set of problems of anti-crisis management to overcome "crisis points" in the business cycle of the enterprise and prevent its bankruptcy is highlighted. An algorithm for managing the organization in crisis by balancing the levels of manageability and adaptability of the business system is presented. Tools are grouped according to the stages of the anti-crisis management process (pre-crisis stage, crisis stage and post-crisis stage). The need to implement tools and methods of preventive anti-crisis management in the activities of domestic enterprises is emphasized. The conditions and limitations of the development of anti-crisis measures are formulated, the choice of anti-crisis management tools is substantiated. On this basis, the goals of the implementation of the anti-crisis strategy are determined and the basic provisions of the strategic plan focused on preventing the crisis and bankruptcy of the enterprise are highlighted.